Foxp3+ Tregs are recruited to the retina to repair pathological angiogenesis - Devy Deliyanti (Nature Portfolio, 2017)
The local immune responses in the eye are attenuated to preserve sight. Surprisingly, Deliyanti et al. show that regulatory T cells (Tregs) take an active role in protecting the eye from neovascularization in oxygen-induced retinopathy, and that interventions that augment the retinal Treg numbers reduce neovascular retinopathy in mice.